Formation of the foundations of digital competence of elementary school students - Kotelevets, K. (Problems of Engineer-Pedagogical Education, 2023)
The article reveals the essence and describes the characteristics of digital competence of primary school students. It highlights that the processes of reforming the education system and the introduction of the Concept of the New Ukrainian School determine the urgency to search for mechanisms to ensure the success of an individual’s life. One of such mechanisms is the formation of digital competence of primary school students. The paper deals with the question related to the relevance of developing hard and soft skills that are nowadays considered to be universal skills which ensure the success of an individual. The analysis of scientific sources is carried out and makes it possible to generalize that digital competence of students in the process of obtaining primary education means the willingness and ability of an individual to use information and communication technologies in order to master the content of primary education. The priority of the research into the development of digital competence of participants in the educational process is revealed. The article actualizes the leading aspect of ensuring the success of the process of developing digital competence of participants in the educational process, and the question of its organization, tracking, timely adjustment and evaluation of outcomes. The content of the New Ukrainian School Concept is analyzed, and it is determined that the graduate of such a school is an educated Ukrainian, a well-developed responsible citizen and a patriot, capable of taking risks and innovation. The reorientation of the content, methods and forms of education in primary school to the formation of students’ soft skills is substantiated. The essence of digital competence of primary school students is defined as a set of skills necessary to work with information in all its representations and forms, and abilities to use information and communication technologies both in professional activity and in everyday life. Five components of digital competence of primary school students are described, namely: basics of computer literacy; information literacy (knowledge and skills of working with information); use of digital resources to solve educational problems; use of mobile applications for communication; and security in the digital environment. Twenty-one criteria for assessing digital competence of primary school students are presented and a qualimetrics approach to assessing this competence is described.